1999
DOI: 10.1111/1467-8489.00076
|View full text |Cite
|
Sign up to set email alerts
|

The valuation of market information from livestock selling complexes

Abstract: The e¤cient operation of livestock markets is contingent upon producers accessing relevant market information which assists adjustment to production and distribution. This article provides an analysis of the value of market information gleaned by producers attending public livestock auctions. The article uses the Travel Cost Method to quantify the value of this information and notes the limitations of applying the Travel Cost Method in this context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Vernimmen et al (2000), Matungul et al (2001), Gong et al (2006), Shiimi (2009) and Jordaan and Grove (2013), in their studies, have suggested that being informed about government policies is an important factor in market participation for small-scale animal producers in developing countries since producers often lack information about their rights and the legislative frameworks. Crase and Dollery (1999) have argued that the limitations of humans may be such that they lack the skills, knowledge and intelligence to process information on products even within a bounded rationality framework. Hence, the more time and energy spent on searching for market information, the higher the ICs (Gong et al, 2007).…”
Section: Sectoral Unfeasibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Vernimmen et al (2000), Matungul et al (2001), Gong et al (2006), Shiimi (2009) and Jordaan and Grove (2013), in their studies, have suggested that being informed about government policies is an important factor in market participation for small-scale animal producers in developing countries since producers often lack information about their rights and the legislative frameworks. Crase and Dollery (1999) have argued that the limitations of humans may be such that they lack the skills, knowledge and intelligence to process information on products even within a bounded rationality framework. Hence, the more time and energy spent on searching for market information, the higher the ICs (Gong et al, 2007).…”
Section: Sectoral Unfeasibilitymentioning
confidence: 99%
“…a5 Unfeasibility due to producers' insufficient professional animal husbandry knowledge/experience. Crase and Dollery (1999), Matungul et al (2001, Gong et al (2007, Kyeyamwa et al (2008) d2 Risk of stress / accident / injury / livestock waste during transport. Hobbs (1996a), Hobbs (1997), Ndoro et al (2015).…”
Section: Sectoral Unfeasibilitymentioning
confidence: 99%
“…Such auctions lower the cost of price discovery for these ranchers, which Coase (1937) argued is the principal source of transaction costs in a market. For example, Crase and Dollery (1999) used the Travel Cost Method to evaluate the importance of the market information provided to sellers.…”
Section: Cattle Auctions and Informationmentioning
confidence: 99%